ANALYSIS OF EFFICACY OF ARTHROSCOPIC PLASTY TECHNOLOGIES OF ANTERIOR CRUCIFORM LIGAMENT OF KNEE JOINT BASED ON ANATOMICAL POSITION OF AUTOGRAFT - V. V. Zayats; A. K. Dulaev; A. V. Dydykin; I. N. Ul’Yanchenko; A. V. Kolomoitsev; A. V. Kovtun (Вестник хирургии имени И.И. Грекова, 2017)
OBJECTIVE. The study compared the efficacy of anatomic and transtibial ACL (anterior cruciform ligament) reconstruction. MATERIALS AND METHODS. The authors analyzed 586 operations at the period from 2010 to 2015. The anatomic ACL-R was performed in the first group of 289 patients (49,3 %). The transtibial ACL-R was carried out in the second group of 297 patients (50,7 %). RESULTS. The adverse outcomes were rarely observed in the first group (p